Perpustakaan Negara Malaysia Jalan Pekeliling Kuala Lumpur / Adenan Omar - Omar, Adenan (Faculty of Architecture, Planning and Surveying, 1983)
Under the Second Malaysia Plan the Federal Governemnt provided an allocation of $2.5 million for the construction of the National Library Building. A 6 acre site was accordingly purchased in 1971 adjacent to Muzium Negara but owing to various factors, construction could not be undertaken early in the Plan period. In 1974 the 6 acre site was appropriated for other purposes. A new site of approximately 5 acres, located along Circular Road adjacent to the San Peng Flats was approved for the National Library in the latter half of 1978. A copy of the site plan is attached. In the meantime, the National Library, which has been growing at a very rapid pace, is occupying rented premises of nearly 0,000 sq.ft. at Wisma Thakurdas/Sachdev, Jalan Raja Laut, at Bangunan Maba, Jalan Hang Jebat as well as an old building at Jalan Perdana. It is essential that the new building for the National Library i s constructed as soons as possible during the TMP period in order to obviate the continued necessity for the National Library to rent premises.